2016
DOI: 10.1002/adhm.201500908
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Activatable MnO‐Based Fluorescence and Magnetic Resonance Bimodal Nanoprobe for Cancer Imaging

Abstract: Stimuli-responsive nanoprobes that combine both fluorescence and magnetic resonance imaging (MRI) are anticipated to be highly beneficial for tumor visualization with high imaging sensitivity. By employing an interfacial templating scheme, a pH-activatable fluorescence/MRI dual-modality imaging nanoprobe is successfully developed based on the coencapsulation of MnO nanoparticles and coumarin-545T inside a hybrid silica nanoshell. To promote cancer cell targeting with high-specificity, the nanoprobes are also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…In our study, HA‐MnO 2 NPs after induced by exposure to H 2 O 2 or GSH in acidic environment attained much higher r 1 relaxivity than that of commercial CA, for example, Gd‐DPTA ( r 1 = 3.5 mM −1 s −1 ). In addition, the r 1 and r 2 relaxivities of HA‐MnO 2 NPs induced by exposure to H 2 O 2 or GSH in acidic environment were higher than or similar to other MnO 2 ‐based NPs previously reported . It has been reported that r 1 relaxivity of MnO 2 can increase in various tumor environments, such as low pH (5.0–6.8), high H 2 O 2 , and high GSH .…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…In our study, HA‐MnO 2 NPs after induced by exposure to H 2 O 2 or GSH in acidic environment attained much higher r 1 relaxivity than that of commercial CA, for example, Gd‐DPTA ( r 1 = 3.5 mM −1 s −1 ). In addition, the r 1 and r 2 relaxivities of HA‐MnO 2 NPs induced by exposure to H 2 O 2 or GSH in acidic environment were higher than or similar to other MnO 2 ‐based NPs previously reported . It has been reported that r 1 relaxivity of MnO 2 can increase in various tumor environments, such as low pH (5.0–6.8), high H 2 O 2 , and high GSH .…”
Section: Resultssupporting
confidence: 74%
“…In addition, the r 1 and r 2 relaxivities of HA‐MnO 2 NPs induced by exposure to H 2 O 2 or GSH in acidic environment were higher than or similar to other MnO 2 ‐based NPs previously reported . It has been reported that r 1 relaxivity of MnO 2 can increase in various tumor environments, such as low pH (5.0–6.8), high H 2 O 2 , and high GSH . Thus, MnO 2 is considered as a novel, activatable tumor environment‐responsive CA for MRI.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The researchers have already explored many methods to enhance the accuracy and efficiency of selective localization in the course of treatment, such as magnetic targeting, molecular targeting, imaging‐guidance, and so on. In particular, the magnetic targeting, which can be achieved by the involvement of iron oxide nanoparticles in the treatment platform, can not only get the physical position of drugs but also realize the imaging (MRI) guided therapy effect simultaneously . Notably, another advantage of magnetic targeting over molecular targeting methods is no dependency on the specific receptor expression (such as the receptor expression variation in normal tissues, or the patient‐to‐patient differentiation) .…”
Section: Introductionmentioning
confidence: 99%
“…[64] Ad ifferent strategy towards complex nanostructures is the co-encapsulation of the different components (including preformed MnO x )i nside polymericorl ipid matrices ( Figure 2D). [32,44] In general terms, the preparation of well-defined manganese oxidesn anostructures other than MnO 2 requires more complex approaches. For example, Hsu et al [44] reported the preparation of MnO NPs through the thermal decomposition of manganese(II)o leatea t2 80 8Cf or 1h.T hermal decomposition protocols are based on the controlled destruction of organometallic compounds in oxygen-and water-free atmosphere,r esulting in the slow availability of metal precursors, thus enabling close [41] B) Fe 3 O 4 @Mn 3 O 4 nanoparticles, [42] C) MnO@Mn 3 O 4 nanoparticles, [43] D) MnO@SiO 2 nanoparticles, [44] E) hollow MnO 2 nanoparticles, [45] F) Fe 3 O 4 /MnO x -GO nanostructures.…”
Section: Manganese Oxidesmentioning
confidence: 99%